Pondok Persulukan Syekh Sulaiman Lubis al-Kholidy: Penggagas Tarekat dan Nasionalisme di Desa Hutapungkut, Mandailing Natal - Sakdiah, Sakdiah; Sazali, Hasan; Purwaningtyas, Franindya (Mahesa Research Center (PT. Mahesa Global Publishing), 2021)
This article discusses the role of Sheikh Sulaiman Lubis al-Kholidy's Islamic boarding school in spreading the teachings of the Naqsyabandiyah Order and the spirit of nationalism in Hutapungkut Village, Mandailing Natal. This study uses a qualitative research method with a historical approach that links various reference sources with the theme being studied. Syekh Sulaiman Lubis al-Kholidy's hut is estimated to have been around since the mid-19th century. Its founder was Sheikh Sulaiman Lubis al-Kholidy who studied tarekat in the villages of Besilam, Langkat and Jabal Qubais, Mecca. The focus of this article is to see how the role played by this Islamic boarding school in building the spirit of nationalism of its followers. In addition, this article also wants to see what socio-political changes have resulted from the presence of this Islamic hut, especially in Hutapungku Village, Mandailing Natal Regency. The results of the research that the authors found were that, apart from being successful in spreading the teachings of the Naqsyabandiyah Order in the Mandailing Natal area, Syekh Sulaiman Lubis also succeeded in instilling the spirit of nationalism amongÂ